Comparison of virtual reality platforms to enhance medical education for procedures - Shah, Nishant K.; Taunk, Neil K.; Maxwell, Russell; Wang, Xingmei; Hubley, Emily; Anamalayil, Shibu; Trotter, Jacob W.; Li, Taoran (Frontiers in Virtual Reality, 2022)
Background: Historically, medical education relied on apprentice-based experiences requiring direct observation in patient cases. Simulation-based education has been shown to improve resident confidence but can be time intensive and difficult to coordinate. The COVID-19 pandemic demonstrated the need to develop distributed educational tools. Virtual reality (VR) platform has been shown to improve resident confidence and proficiencies. This pilot study compared educational and cost effectiveness of low-cost cardboard viewer VR (CVVR) and commercially available integrated headset VR (IHVR). Methods/Materials: We created a 2D, 360-degree VR video of an intracavitary brachytherapy case for treatment of cervical cancer. Radiation oncology residents from a single ACGME-accredited training program were recruited and randomized to IHVR or CVVR. Both groups were given unlimited access to their randomized technology. Each resident performed a timed intracavitary procedure on a simulator while 5 implant quality metrics were recorded. A pre- and post-simulation questionnaire assessed self-confidence, procedural knowledge, and perceived usefulness of VR technology. Results: There were 13 residents, including four post-graduate year (PGY)-2, three PGY-3, two PGY-4, and four PGY-5, in the study. Both VR technologies improved self-perceived overall confidence. Average time required for implant (mean: CVVR - 200 seconds vs. IHVR - 235 seconds, p=0.38) and median objective proficiencies of implant quality (5/5 in both group, p=0.56) were similar. There was no difference between CVVR and IHVR as useful, enjoyable and engaging educational tool. Both groups would recommend the technology to another trainee. IHVR-based program would cost 33x more than CVVR-based program based on an assessment of US-based programs. Conclusion: CVVR is a cost-effective alternative to a IHVR as a virtual video-based education tool.